2010
DOI: 10.1007/s10695-008-9298-y
|View full text |Cite
|
Sign up to set email alerts
|

Social rank modulates brain arginine vasotocin immunoreactivity in false clown anemonefish (Amphiprion ocellaris)

Abstract: The brain nanopeptide arginine vasotocin (AVT) and its mammalian homolog arginine vasopressin are involved in the regulation of social and reproductive behavior. We investigated the relationship between social rank formation and the brain AVT system in the false clown anemonefish (Amphiprion ocellaris), which forms a social rank that leads to sex differentiation in higher-ranked individuals. Tanks of three sexually immature fish were kept for 90 days and each fish's behavior was observed once a month. The soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…However, such species-specific differences in the effects of AVT on aggression likely result from the use of different behavioral testing methods and not opposing responses to AVT in the lateral septum . Varying relationships between neural AVT and aggression (or specific dominant vs. subordinate phenotypes) have also been reported in fish and reptiles [Larson et al, 2005;Lema, 2006;Ohya and Hayashi, 2006;Santangelo and Bass, 2006;Dewan et al, 2008;Greenwood et al, 2008;Hattori and Wilczynski, 2009;Iwata et al, 2010]. Collectively, these studies highlight the complexity of AVP/AVT's role in aggression and how this evolutionarily conserved system can contribute to context-specific behavioral responses.…”
Section: Introductionmentioning
confidence: 86%
“…However, such species-specific differences in the effects of AVT on aggression likely result from the use of different behavioral testing methods and not opposing responses to AVT in the lateral septum . Varying relationships between neural AVT and aggression (or specific dominant vs. subordinate phenotypes) have also been reported in fish and reptiles [Larson et al, 2005;Lema, 2006;Ohya and Hayashi, 2006;Santangelo and Bass, 2006;Dewan et al, 2008;Greenwood et al, 2008;Hattori and Wilczynski, 2009;Iwata et al, 2010]. Collectively, these studies highlight the complexity of AVP/AVT's role in aggression and how this evolutionarily conserved system can contribute to context-specific behavioral responses.…”
Section: Introductionmentioning
confidence: 86%
“…This difference has been documented in several species of sex changing fish such as wrasse, goby, and anemone fish where sex specific behavior has been correlated with AVT cell populations in the POAH that vary in relation to sexual state (Godwin et al, 2000;Grober and Sunobe, 1996;Iwata et al, 2008). The AVT V1a type receptor has been implicated in the control of certain male behaviors in different vertebrate groups because administration of an AVP V1a specific antagonist can disrupt these behaviors.…”
Section: Introductionmentioning
confidence: 96%
“…An observable relationship between body mass and the number and size of AVT and IT-ir neurons was not evident. Our previous study [5] indicated that the number and size of AVT-ir neurons in the POA were notably influenced by body mass after 90 days of pairing, and the results with mass-corrected data showed that the number of AVT-ir neurons in the magnocellular layer declined with increasing hierarchical dominance. This contradicts our present results, which show the same trend with or without mass correction (data not shown).…”
Section: Discussionmentioning
confidence: 85%
“…Preadsorption tests on anti-AVT and anti-IT sera were omitted because their specificity had already been verified [5,[7][8][9][10].…”
Section: Brain Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation